2021
DOI: 10.30802/aalas-jaalas-20-000136
|View full text |Cite
|
Sign up to set email alerts
|

Transcutaneous Ultrasound Guided Intraovarian Injection in Rats (Rattus norvegicus)

Abstract: The goal of this study was to develop a method for ultrasound-guided percutaneous intraovarian injection in Wistar rats.Intraovarian administration of chemicals or needle aspiration of the ovary has been undertaken in some species, includinghumans, equines, and bovines. In rodents, which are widely used in scientific research, a technique for intraovarian injectionwithout surgical exposure of the organ has not been described. The current study standardized the procedure of ovarianpercutaneous injection of 0.9%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The length, width, and area of the ovaries were measured, and the presence and quantity of ascites in the abdomen and around the ovary were noted. The quantity of ascites in the peritoneum was graded as mild (I), moderate (II), and high (III) [ 17 , 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…The length, width, and area of the ovaries were measured, and the presence and quantity of ascites in the abdomen and around the ovary were noted. The quantity of ascites in the peritoneum was graded as mild (I), moderate (II), and high (III) [ 17 , 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…Intraovarian percutaneous injection of 150 μl of solution was performed, guided per ultrasonography as previous described [ 27 ], in both ovaries, as follows: group GC (control) - saline solution; group G10 - calcium chloride 10% diluted in ethanol 95%; group G20 - calcium chloride 20% diluted in ethanol 95%. Previous practice on rats’ reproductive tracts showed that the volume of 150 μl of saline solution would be sufficient to fulfil the in rats of same age (90 days-old).…”
Section: Methodsmentioning
confidence: 99%